The Role of Balai Harta Peninggalan as Curator in The Management and Settlement of Bankrupt Assets - F. Sekar Widiarini; Teddy Anggoro (LEGAL BRIEF, 2022)
When an application for Bankruptcy occurs by the Debtor or Creditor, as well as the parties authorized to file a bankruptcy application, the role of the Curator is needed as the administrator and performs the settlement of the bankruptcy estate. In Law Number 37 of 2004 concerning Bankruptcy and Postponement of Obligation for Payment of Debt, it provides a definition that the Curator is the Balai Harta Peninggalan or an individual who is appointed by the Court to manage and settle the assets of the Bankrupt Debtor under the supervision of the Supervisory Judge. In current practice, the role of Balai Harta Peninggalan as Curator in Bankruptcy seems to have diminished since the emergence of the role of Private Curator. In order to use the services of a Curator, the appointment of a Curator to manage and settle the bankruptcy estate may be requested by the Debtor or Creditor in Bankruptcy for appointment. However, when the Debtor or Creditor does not apply for the appointment of a Curator to manage and settle the bankruptcy estate, the Supervisory Judge will appoint the Curator from the Balai Harta Peninggalan to manage and settle the bankruptcy estate belonging to the Bankrupt Debtor. As a result of this arrangement, the role of Balai Harta Peninggalan as Curator becomes noticeably limited, because only when the Debtor or Creditor does not apply for the appointment of a Curator, the role of the Balai Harta Peninggalan as Curator will emerge. So, in this paper, the writer wants to know how the role of Balai Harta Peninggalan is in managing and settling bankrupt assets, which later can be the basis for deciding whether to use the services of Balai Harta Peninggalan as Curator or the services of a Private Curator in the management and settlement of bankrupt assets.